Digitalization of Industry and Education - Ostapenko Mariya (EDP Sciences, 2021)
The fourth industrial revolution, associated with the introduction of robotics, cyber-physical systems, artificial intelligence, neural networks, affects all spheres of human life. There is a need for specialists with the appropriate skills. The article discusses the elements of Industry 4.0: Internet of Things, robotization, PLM system. The impact of digitalization on the educational sector is also considered.